The practice of political theory : Rorty and continental thought - Chin, Clayton (New directions in critical theory, 2018)
Recent political thought has grappled with a crisis in philosophical foundations: how do we justify the explicit and implicit normative claims and assumptions that guide political decisions and social criticism? In The Practice of Political Theory, Clayton Chin presents a critical reconstruction of the work of Richard Rorty that intervenes in the current surge of methodological debates in political thought, arguing that Rorty provides us with unrecognized tools for resolving key foundational issues. Chin illustrates the significance of Rorty's thought for contemporary political thinking, casting his conception of "philosophy as cultural politics" as a resource for new models of sociopolitical criticism. He juxtaposes Rorty's pragmatism with the ontological turn, illuminating them as alternative interventions in the current debate over the crisis of foundations in philosophy. Chin places Rorty in dialogue with continental philosophy and those working within its legacy. Focused on both important questions in pragmatist scholarship and central issues in contemporary political thought, The Practice of Political Theory is an important response to the vexed questions of justification and pluralism.